2019
DOI: 10.1177/1360780419888927
|View full text |Cite
|
Sign up to set email alerts
|

‘Sociologists Shouldn’t Have to Study Statistics’: Epistemology and Anxiety of Statistics in Sociology Students

Abstract: Worry about learning maths and statistics has been widely researched internationally but very little of this work has focussed on sociology. It is well documented that sociology students can be reluctant to engage with statistical methods. This article provides an exploration of the relationship between anxiety of statistics and its antecedents in sociology students. The analyses presented are based upon data collected from over 30 universities in the UK and is the most comprehensive sample of its type. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
(91 reference statements)
1
19
0
Order By: Relevance
“…It seems that the way in which university students perceive their ability for statistics can tended to present an inverse relationship with SA in our analyses. 9,31,52,53 Further insights from our meta-analysis attest to this trend, showing that across studies, the higher a student's reported assuredness in their capacity for statistics (self-efficacy), the lower their presentations of SA. This, perhaps, indicates a prospect for statistics instructors to employ teaching strategies and encourage learning behaviours which aim to increase self-efficacy among students to reduce SA.…”
Section: Do Self-perceptions Regarding Statistics Course and Instruct...mentioning
confidence: 64%
See 2 more Smart Citations
“…It seems that the way in which university students perceive their ability for statistics can tended to present an inverse relationship with SA in our analyses. 9,31,52,53 Further insights from our meta-analysis attest to this trend, showing that across studies, the higher a student's reported assuredness in their capacity for statistics (self-efficacy), the lower their presentations of SA. This, perhaps, indicates a prospect for statistics instructors to employ teaching strategies and encourage learning behaviours which aim to increase self-efficacy among students to reduce SA.…”
Section: Do Self-perceptions Regarding Statistics Course and Instruct...mentioning
confidence: 64%
“…Most of the studies examined SA and participant gender and found conflicting results. In Ralston's research, women had a higher probability of reporting SA 52 . Baloğlu and colleagues reported higher levels of SA among women, but only on the Interpretation Anxiety and Test/class Anxiety subscales of the STARS 55 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Macher et al [27] contended that anxiety has a positive influence on learning behaviors. Nonetheless, the assertion that introductory statistics courses in social sciences induce anxiety, and subsequent negative outcomes underpin many studies and literature reviews [28]. Despite a growing body of literature comparing performance as manifesting in POE and F2F statistics students [29], the scholarly research comparing the manifestations of Statistics Anxiety in F2F, POE, and ERT environments, and their relation to academic misbehavior is scanty.…”
Section: Theoretical Background 21 Anxietymentioning
confidence: 99%
“…Otherwise stated, current socioeconomic and health circumstances (i.e., the COVID-19 pandemic) have revealed that there is a need to promote the development of skills and knowledge focusing on the formation of statistically literate citizens [23], for which statistics education is imperative. Hence, identifying students' propensity to develop statistics anxiety in introductory statistics courses as determined by their specific personality traits may allow to prepare instructors for intervening [24] and preventing academic dishonesty whenever needed.…”
Section: Introductionmentioning
confidence: 99%